Characterization of the sugar cane (Saccharum Officinarum) transportation process for non-centrifugal sugar production - Cubillos-Varela, Alfonso (2025)
The agroindustry of not centrifugal sugar (NCS) production is the second agricultural sector in Colombia, due to its contribution to the generation of jobs and planted area. Despite its contribution to the national economy, this agroindustry faces a series of technological problems that require the modernization of traditional production processes, such as the transportation of sugar cane from the crop plots to the processing point (trapiche), which continues to be developed using pack animals. The objective of this work was to characterize the transportation process of sugar cane (Saccharum officinarum) to produce NCS through the definition and measurement of logistical indicators for the transportation of agricultural products. The research was carried out during the months of April and October 2021 in five municipalities in the department of Boyacá (Colombia) where NCS production takes place, through the collection and analysis of information on productive activity and field monitoring of the cane transportation process with the use of pack animals. The results allowed us to characterize, evaluate current transportation methods and define a baseline of the sugarcane transportation process based on logistical transportation indicators, which serve as a reference for the comparison, selection, or design of new transportation systems for agricultural products.